An actionable understanding of societal transitions: the X-curve framework - Aniek Hebinck; Gijs Diercks; Timo von Wirth; P. J. Beers; Lisa Barsties; Sophie Buchel; Rachel Greer; Frank van Steenbergen; Derk Loorbach (Sustainability Science, 2022)
Sustainability transition research seeks to understand the patterns and dynamics of structural societal change as well as unearth strategies for governance. However, existing frameworks emphasize innovation and build-up over exnovation and break-down. This limits their potential in making sense of the turbulent and chaotic dynamics of current transition-in-the-making. Addressing this gap, our paper elaborates on the development and use of the X-curve framework. The X-curve provides a simplified depiction of transitions that explicitly captures the patterns of build-up, breakdown, and their interactions. Using three cases, we illustrate the X-curve’s main strength as a framework that can support groups of people to develop a shared understanding of the dynamics in transitions-in-the-making. This helps them reflect upon their roles, potential influence, and the needed capacities for desired transitions. We discuss some challenges in using the X-curve framework, such as participants’ grasp of ‘chaos’, and provide suggestions on how to address these challenges and strengthen the frameworks’ ability to support understanding and navigation of transition dynamics. We conclude by summarizing its main strength and invite the reader to use it, reflect on it, build on it, and judge its value for action research on sustainability transitions themselves.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Population dynamics and genotypic richness of threatened Acropora species and their hybrid in the U.S. Virgin Islands - Hannah F. Nylander-Asplin; Ronald L. Hill; Jennifer C. Doerr; Lisa Greer; Nicole D. Fogarty (Coral Reefs, 2021)
Acropora cervicornis and A. palmata have experienced substantial losses in coral cover throughout the Caribbean, but their hybrid ( A. prolifera ) appears to be increasing at some sites. The shifts in relative abundance could result from hybridization with subsequent asexual fragmentation, recent increased hybridization, or a disproportionate loss in the parental species. Here, acroporid taxa from three U.S. Virgin Islands sites were genotyped revealing 35 hybrid genotypes, suggesting multiple hybridization events. Genotypic richness in A. cervicornis (0.62), A. prolifera (0.64), and A. palmata (0.68) was not significantly different across sites. To further explore acroporid dynamics at these sites, we analyzed existing photo transects from 2009 to 2017 to reveal significant losses of A. cervicornis but stable hybrid percent cover. High genotypic richness and stable populations suggest acroporid hybrids may become the primary shallow reef-builders in some locations previously occupied by the parental species.

Age and intraspecific diversity of resilient Acropora communities in Belize - Adele Irwin; Lisa Greer; Robert Humston; Meghann Devlin-Durante; Paul Cabe; Halard Lescinsky; Karl Wirth; H. Allen Curran; Iliana B. Baums (Coral Reefs, 2017)